Research Progress on Traditional Chinese Medicine Treatment Strategies for Gallstone Disease - Yan, Zhiqiang; Yang, Xingwu (Journal of Contemporary Medical Practice, 2025)
Gallstone disease is a common clinical digestive disorder with a steadily rising global incidence in recent years. Traditional Chinese medicine (TCM) offers unique advantages in preventing and treating gallstones. Based on the theory of “liver qi stagnation and gallbladder dysfunction,” TCM demonstrates significant efficacy in alleviating clinical symptoms and reducing recurrence rates through syndrome differentiation and treatment. This paper systematically reviews the latest research advances in TCM treatment strategies for cholelithiasis, comprehensively elaborating on theoretical understanding, therapeutic approaches (internal and external treatments), and mechanisms of action. Studies indicate that TCM exerts a significant role in the prevention and treatment of cholelithiasis through multi-pathway, multi-level integrated regulation. Particularly, the promotion and application of integrated Chinese and Western medicine treatment models provide patients with superior diagnostic and therapeutic options. Future efforts should focus on deepening mechanism-of-action research, conducting high-quality clinical trials, and advancing the standardization and internationalization of TCM.